Ag Nanoparticles Decorated TiO2 Thin Films with Enhanced Photocatalytic Activity (Phys. Status Solidi A 14∕2019). Issue 14 (23rd July 2019) - Veziroglu, Salih; Ghori, Muhammad Zubair; Obermann, Anna‐Lena; Röder, Katharina; Polonskyi, Oleksandr; Strunskus, Thomas; Faupel, Franz; Aktas, Oral Cenk
Abstract : Photocatalysis In article number1800898, Salih Veziroglu, Franz Faupel, Oral Cenk Aktas, and co‐workers present a facile method to prepare Ag nanoparticles (NPs) decorated TiO2 thin film by photocatalytic deposition. The presented method allows easy controlling size, morphology and distribution density of Ag NPs on TiO2 to achieve a high photocatalytic activity.